Arts, Creativity, and Social Media: A Critical Review of the Dalinian Universe on Instagram - Elías-Zambrano, Rodrigo; Cabezuelo-Lorenzo, Francisco (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This work analyses the presence of the life and work of the brilliant Spanish artist Salvador Dalí on social networks, with special attention to the most visual of them all: Instagram. Emphasis is placed on the study of the profile of the brilliant Catalan author as an example for inspiration and creativity in today's digital society. This work attempts to identify what profiles and what content has been created on networks about the Catalan, with special attention to educational, institutional, and creative content, especially of a scientific, academic, and informative nature, especially in the case of reinterpretations of his work by new contemporary artists.